2004
DOI: 10.1038/sj.bjp.0705755
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of calcium homeostasis in adenocarcinoma cell line A549 and its Taxol‐resistant subclone

Abstract: Drug resistance is a fundamental problem in cancer chemotherapy. Intracellular calcium concentration ([Ca2+]i) may play a role in the development of chemoresistance. We investigated the regulatory role of [Ca2+]i in Taxol resistance in the non‐small‐cell lung cancer cell line A549 and its chemoresistant subclone A549‐T24. Measurement of cytosolic calcium ([Ca2+]c) in single cells and cell populations revealed similar levels of basal calcium in the two cell lines. However, a reduced response to thapsigargin (a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(47 citation statements)
references
References 62 publications
7
40
0
Order By: Relevance
“…51 As shown in Fig. 7C, the enlarged GFP-LC3B puncta induced by knockdown of NEDD4 are colocalized with ATP2A2 in both control and rapamycin-treated samples, which is consistent with the results in Fig.…”
Section: Depletion Of Nedd4 Induced Aggregation Of Lc3 Puncta In Cellssupporting
confidence: 80%
“…51 As shown in Fig. 7C, the enlarged GFP-LC3B puncta induced by knockdown of NEDD4 are colocalized with ATP2A2 in both control and rapamycin-treated samples, which is consistent with the results in Fig.…”
Section: Depletion Of Nedd4 Induced Aggregation Of Lc3 Puncta In Cellssupporting
confidence: 80%
“…Moreover, altered intracellular calcium homeostasis may contribute to the paclitaxel-resistant phenotype (35). Microarray analysis in this study revealed a decline of S100A8/S100A9 expression in PC-3-TxR cells compared with parent PC-3 cells.…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, neuronal cells exposed to oxygen and glucose deprivation activate the Na þ /Ca 2þ exchanger NCX1, which is known to be a target protein of sorcin (14), and this is correlated with accumulation of Ca 2þ into the ER, and prevention of ER stress and apoptosis (42). Furthermore, increased levels of Ca 2þ in the ER have also been correlated with MDR phenotypes in cancer cells (41,43). Thus, it is intriguing to speculate that sorcin isoforms are both involved in regulating Ca 2þ homeostasis in separate cell compartments and that this function is relevant for their antiapoptotic activities in tumor cells.…”
Section: Discussionmentioning
confidence: 99%